Effects of yeast extract (YE) and peptone (P) on sago hampas hydrolysate (SHH) for bioethanol production - Nur Na'imah, Hussein (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Nitrogen sources are very crucial in the fermentation process in order to provide nutrients to the yeast cell so that it can produce high amount of bioethanol. This study is focuses on batch ethanol fermentation utilizing 50 g/L glucose of sago hampas hydrolysate (SHH) with the supplementation yeast extract (3 g/L) or peptone (1 g/L). The fermentation was conducted in 100 mL working volume, agitated at 100 rpm, initial pH of 5.5- 5.6 and maintains at (30t ± 0.5). Based on the results, it was observed that glucose from SHH was found to be the good carbon source for production of bioethanol compared with commercial glucose. Furthermore, out of two nitrogen sources (peptone and yeast extract) tested, peptone was preferable as less amount (1 g/L) was used compared to yeast extract (3 g/L). However the bioethanol production was comparable (21.42 g/L) for both nitrogen sources. From the present study, it can be concluded that glucose from SHH can be an attractive feedstock for bioethanol production from both economic stand point as well as environment friendly.